Rare cases of haemoglobin variant presented with isolated erythrocytosis - Nahanthiran, Subithira; N. M., Hafidzah; N., Syirah; E., Ezalia; Faridah; M N, Sabariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Haemoglobinopathies presenting with erythrocytosis is relatively rare. The clinicians might mistakenly diagnose such patients with other causes of erythrocytosis such as myeloproliferative neoplasm, etc instead of haemoglobinopathies. Here, we described two cases of haemoglobin variant, namely Haemoglobin Johnstown (Hb Johnstown) and Haemoglobin Bethesda (Hb Besthesda) that were detected following various futile investigations for persistent erythrocytosis. For both cases, the two main screening methods used were capillary electrophoresis (CE) and high performance liquid chromatography (HPLC). Approximately 30% of the high affinity haemoglobin (Hb) are not detected by electrophoresis method, however, in some cases, a variant Hb peak can be seen in chromatography method. Thus, a high index of suspicion of such diagnosis is utmost important as to not to miss the definitive diagnostic test by DNA analysis.